Konstitusionalitas Pernikahan Poligami Muslim di Uganda: Sebuah Komentar atas Perkara Women's Probono Initiative melawan Jaksa Agung (Permohonan Konstitusional No. 12 Tahun 2021) [2025] UGCC 6 (10 Juli 2025) - Jamil Ddamulira Mujuzi (Badan Strategi Kebijakan Hukum, 2026)
The Constitution of Uganda (1995) neither expressly permits nor prohibits polygamy. However, its drafting history shows that the delegates were aware that some Ugandans were in polygamous relationships (in particular polygyny). Neither the Customary Marriage (Registration) Act nor the Marriage and Divorce of Mohammedans Act expressly provides for polygamy. However, customary and Muslim marriages are potentially polygamous and there are many instances in which men in such marriages have several wives. There is no known ethnic or religious group in Uganda that practices polyandry. Unlike in some African countries, in Uganda polyandry is not an offence. The research question to be answered in the paper is whether polygamy is constitutional. In other words, whether the constitution could be interpreted as permitting polygamy. In Women's Probono Initiative v Attorney General (2025), the Constitutional Court of Uganda dealt with the question of whether polygynous marriages (both customary and Muslim) are unconstitutional on the ground that, inter alia, they discriminated against women (for example, by not allowing polyandry); they amount to torture and they violate the right to human dignity. The Court also dealt with the question of whether Islamic law which provides that a wife inherits less than a husband is discriminatory. The Court answered all the above questions in the negative. In this article, the author argues that the Court interpreted the Constitution correctly. However, the author suggests ways in which its decision could have been strengthened. The author also highlights some of the future implications of the Court’s decision.